Investigating the physico-mechanical properties of bamboo fiber reinforced composite (BFRC) plates and its effects on strengthening of rc beams externally - Tong, Foo Sheng (2018)
The synthetic fiber reinforced polymer (FRP) composite is an effective method for strengthening the reinforced concrete (RC) member externally. However, high cost, environmental impact, and adverse effects on human health are the major limitation of FRP composite. Thus, the natural fiber reinforced polymer composite (NFRPC) for the strengthening of RC structure is the trending interests in the construction industry. This study presented an experimental investigation on the structural behaviour of RC beams with openings in shear and flexure strengthened using bamboo fiber reinforced composite (BFRC) plates. The purposes of this work are to characterize the physico-mechanical properties of Gigantocholoa scortechinii Gamble (G. scortechinii) fiber and unidirectional BFRC plate. The load-deflection, cracking patterns, and failure mode of BFRC plates strengthened RC beams were also studied. The bamboo culms were treated with different sodium hydroxide (NaOH) concentrations (0, 5, 10, and 15 %) and soaking durations (0, 24, 48, and 72 hours) before subjected to the mill rolling process. The physico-mechanical characterizations were performed to evaluate the optimum treatment parameters for the suitability of fiber as reinforcement in the polymer composite. The BFRC plates were fabricated using an open mould hand lay-up method with different types of thermoset matrix (epoxy, polyester, and vinylester resin) and various fiber loadings (0, 10, 20, 30, and 40 %). The physico-mechanical properties of BFRC plates were examined to determine the optimal mix ratio. A total of 12 beams were tested in Phase 1 (shear strengthening) and Phase 2 (flexural strengthening) under four-point bending until failure. Each phase consists of two control beams, two beams of which was tested with or without the strengthening of BFRC plates. For flexural strengthening, the BFRC plates were bonded at the bottom soffit along the middle span, whereas the BFRC plates were bonded at both top and bottom chords of the openings for shear strengthening. From the obtained results, the surface morphology, crystallinity index, thermal stability, and tensile properties of fiber showed a gradual improvement with increasing NaOH concentrations and soaking durations due to the removal of non-cellulosic constituents. The bamboo fiber treated at 10 % concentrations and 48 hours presented the most outstanding physico-mechanical properties among all the treatment conditions. The physico-mechanical properties of the BFRC plates were enhanced with the increase of fiber content regardless the type of matrix. At 40 % of fiber loading, the bamboo fiber reinforced with the epoxy matrix (BFREC) was confirmed as the optimum ratio by exhibiting the highest physico-mechanical properties. The inclusion of large circular openings in the shear zones led to a reduction in ultimate load by 53.5 %. As compared to the beam with unstrengthened openings, the regained beam capacity by shear strengthening was 52.14 %. The ultimate load-carrying capacity of the flexural strengthened beams had improved the failure load by 7 %. The strengthened beams also exhibited higher first crack load. Both flexural and shear strengthening effectively mitigated the cracks propagation and improved the beam ductility. The obtained findings indicate that the unidirectional BFREC plate could be utilized as external strengthening material for structural strengthening.